ServiceMap: Providing Map and GPS Assistance to Service Composition in Bioinformatics. - Tan, W; Zhang, J; Madduri, R; Foster, I; Roure, D; Goble, C (IEEE, 2011)
The wide use of Web services and scientific workflows has enabled bioinformaticians to reuse experimental resources and streamline data processing. This paper presents a follow-up work of our network analysis on the myExperiment, an online scientific workflow repository. The motivation comes from two common questions raised by bio-scientists: 1) Given the services that I plan to use, are there other services usually used together with them? and 2) Given two or more services I plan to use together, is there an operation chain to connect them based on others' past usage? Aiming to provide a system-level GPS-like support to answer the two questions, we present ServiceMap, a network model established to study the best practice of service use. Two approaches are proposed over the ServiceMap: association rule mining and relation-aware, cross-workflow searching. Both approaches were validated using the real-life data obtained from the myExperiment repository. © 2011 IEEE.